2018
DOI: 10.1097/j.pain.0000000000001385
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid, derived from the desert lavender Hyptis emoryi, attenuates paclitaxel-, HIV-, and nerve injury–associated peripheral sensory neuropathy via block of N- and T-type calcium channels

Abstract: The Federal Pain Research Strategy recommended development of nonopioid analgesics as a top priority in its strategic plan to address the significant public health crisis and individual burden of chronic pain faced by >100 million Americans. Motivated by this challenge, a natural product extracts library was screened and identified a plant extract that targets activity of voltage-gated calcium channels. This profile is of interest as a potential treatment for neuropathic pain. The active extract derived from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 90 publications
0
59
0
Order By: Relevance
“…Betulinic acid (BA), a natural pentacyclic triterpenoid, has gained considerable attention in recent years for its strong biological and medicinal properties [39]. Increasing evidence suggest that BA plays a substantial role in the treatment of various nervous system diseases such Alzheimer's disease [40] peripheral neuropathies [41]. Spinal cord injury is a devastating and common disease that in icts substantial physiological, emotional, and economic damage to patients, their families and societies worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Betulinic acid (BA), a natural pentacyclic triterpenoid, has gained considerable attention in recent years for its strong biological and medicinal properties [39]. Increasing evidence suggest that BA plays a substantial role in the treatment of various nervous system diseases such Alzheimer's disease [40] peripheral neuropathies [41]. Spinal cord injury is a devastating and common disease that in icts substantial physiological, emotional, and economic damage to patients, their families and societies worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of Ca v channel mRNA within dorsal root ganglion neurons have been demonstrated in paclitaxeltreated mice, and Ca v channel antagonists (gabapentin and ethosuximide) effectively reduce hyperalgesia in rodents with paclitaxel-and vincristine-induced CIPN [17]. Many studies have confirmed a crucial role of N-type and T-type Ca v channels in paclitaxel-induced CIPN [74] as well as a key role of T-type Ca v channels in CIPN caused by vincristine [89].…”
Section: Ca V Channelsmentioning
confidence: 99%
“…Altered peripheral nerve excitability has also been implicated in CIPN development. The altered expression and functional impairment of voltage-gated sodium (Na v ), voltage-gated potassium (K v ), voltage-gated calcium (Ca v ) and transient receptor potential family (TRP) channels are regarded as the most prominent phenomena underlying CIPN caused by the platinum derivatives vincristine, paclitaxel and bortezomib [17,74].…”
Section: Changes In Neuronal Excitabilitymentioning
confidence: 99%
“…T-type currents are up-regulated in various models of chronic pain, such as chronic constriction injury, spinal nerve ligation, STZ-diabetes, the carregin pain model, and drug-induced diabetic neuropathy (Jagodic et al, 2007(Jagodic et al, , 2008Melrose et al, 2007;Takahashi et al, 2010;Marger et al, 2011;Watanabe et al, 2015;Li et al, 2017;Bellampalli et al, 2019). Ca V 3.2 can be upregulated by increased expression of USP5, which interacts with and de-ubiquitinates these channels thereby decreasing their degradation (Garcia-Caballero et al, 2014;Stemkowski et al, 2016).…”
Section: Introductionmentioning
confidence: 99%